Beyond Flexibility: Exploring Motivation Factors Influencing Work Satisfaction in the Gig Workforce - Ramya Singh; Archana Sharma; Manish Mishra (Journal of Economics and Business Aseanomics, 2024)
This study examines factors influencing job satisfaction among gig workers in Lucknow's food delivery sector, focusing on flexibility, motivation, and work characteristics. Data from 530 workers affiliated with platforms like Swiggy, Zomato, and Eat Sure were analysed to understand these dynamics. Findings reveal that flexibility in work schedules significantly enhances job satisfaction by enabling workers to balance personal and professional responsibilities effectively. Additionally, motivation, particularly through intrinsic factors like personal growth, recognition, and achievement, plays a pivotal role in job satisfaction, underscoring the importance of fulfilling work. Positive work characteristics such as job autonomy and task variety also contribute substantially to satisfaction levels. Autonomy allows gig workers to make decisions and manage tasks independently, while task variety reduces monotony, keeping work engaging and stimulating. These factors collectively foster a satisfying work experience within the gig economy. The study highlights the importance of organizational policies that promote flexibility, intrinsic motivation, and worker centre environments to enhance well-being and retention among gig workers. By prioritizing these aspects, gig platforms can improve job satisfaction and worker productivity, contributing to the sustainability and growth of the gig economy. These insights offer practical implications for improving gig work conditions, creating a more supportive and satisfying environment for gig workers in the evolving platform economy.